(untitled) (Revista Española de Fisiología, 1966)
We test many methods to measure the amount of histamine in urine and we take from each known method a part and forin a new and original method which allows us to determine with great accuracy the total amount of histamine in the uriníƒe of rats. The results that we have obtained by testing normal rats in the elimination of urine over a period of 24 h was 4.6060 jig with a fluctuation between 6.9522 ng and 3.1879 pg. The results in rats operated on for adrenal capsules was 27.5282 pg of histamine for a period of 24 h of urine with a fluctuation between 42.6868 pg and 17.8624 pg. The food of the rats does not inferiere with our results because both the normal and the operated rats had the same diet. The temperature ist a very important factor to be checked, both in normal and in adrenalectomizades rats, beacause the results are subject to variations. In all experiments the results were blocked with an antihistamine of sintesis.